(untitled) (Economics and region, 2025)
The article examines the current state of Ukraine’s transport sector and identifies key obstacles to its economic development. The article analyses structural issues, the impact of war, and macroeconomic instability. The research outlines a sharp decline in freight volumes since the beginning of full-scale invasion and limited recovery in subsequent years. Key challenges include outdated infrastructure, low investment attractiveness, labor shortages, and regulatory uncertainty. The study emphasizes the need for systemic reforms, state support, and integration with EU logistics networks as crucial conditions for sustainable sectoral recovery and long-term competitiveness. Particular attention is paid to the prospects for Ukraine’s integration into European logistics networks and the development of public-private partnerships as conditions for ensuring sustainable development of transport infrastructure and strengthening the competitiveness of the industry in the long term.